Language Attitudes on English Informal Learner of Non-English Graduate through Lifespan - Amaliah, Amaliah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
Globalization has produced cutting-edge technology that allows people, especially young people, to access information anywhere. Blommaert calls globalization a historical keyword. Despite their similarities, the process of globalization is revolutionary in scope, complexity and dimensions. Over time, globalization can change locations, people, societies, cultures, economies, education, technology, and markets. Many generations consider English to be a universal language. This research is qualitative in nature. Creswell states that qualitative research investigates group intentions in social or human matters. Qualitative research evaluates participants' meaning in this way. Qualitative research uses specific methods to investigate social or human problems. Problem-oriented qualitative research collects data about primary object phenomena. Because it can store and replicate the most profound events and deal with complexity, moral relativism, and live animals, this research uses narrative inquiry. Narrative humanizes humans through the creation and restructuring of stories. Based on interviews and tables about language attitudes among casual English learners across the age range, respondents are very enthusiastic about the English skills learned on YouTube. Baker (quoted in Thuan) says that effective language learners develop a favorable attitude toward their language, which must be taken into account when defining language acquisition attitudes. Divita's lifelong theory helped her learn English. Since learning English, respondents have increased substantially, according to the time scale interview. When the respondent learned English on YouTube informally, he found many channels helpful. Language variation and evolution can be better understood with life span studies, and statistics show that respondents want to learn English. The problem of researching student attitudes by age is solved. The research found that respondents now enjoy their skills across a lifetime, spanning periods and life events. The author concludes that respondents prefer learning English informally. He enjoys learning English on YouTube, which he has used since childhood. This research should investigate respondents' local language skills before and after learning English and whether they prefer formal or informal English learning.